Molecular characterization and mapping of Fgf21 gene in a foodfish species asian seabass. - Le Wang; Jun Hong Xia; Xiao Jun Liu; Peng Liu; Zi Yi Wan; Gen Hua Yue (PLoS ONE)
Fgf21 is a newly discovered fibroblast growth factor. It is typically induced by fasting and plays important roles in the regulation of glucose and lipid metabolisms and energy balance in mammals, whereas potential functions of this gene in teleosts are still unknown. We identified the Fgf21 gene and studied its functions in Asian seabass (Lates calcarifer). The cDNA of the Fgf21 encoded a protein with 206 amino acids. Analysis of DNA and amino acid sequences of Fgf21 genes revealed that the sequences and structure of the Fgf21 genes were highly conserved in vertebrates. Real-time PCR revealed that Fgf21 was exclusively expressed in the intestine and kidney, which was different from the expression profiles of mammals. Fgf21 was down-regulated under fasting, whereas it was significantly increased during the LPS challenge. Exogenous recombinant FGF21 significantly suppressed the appetite of Asian seabass. Our data suggest that Fgf21 plays a role in energy regulation and acute phase response in Asian seabass, and may have different functions in fish and mammals. In addition, we identified one SNP in Fgf21. By using this SNP, the gene was mapped on the linkage group 23, where a suggestive QTL for growth was mapped previously. Association mapping identified significant associations between Fgf21 genotypes at the SNP and growth traits. These results not only provide important information of the functions of Fgf21, but also suggest that the SNP in this gene can be used as a marker in selecting fast-growing individuals of Asian seabass.